2012
DOI: 10.1063/1.4759120
|View full text |Cite
|
Sign up to set email alerts
|

Passively Q-switching induced by gold nanocrystals

Abstract: Passive Q-switching was experimentally demonstrated in an erbium-doped fiber laser (EDFL) by using gold nanocrystals (GNCs). The GNCs were mixed with sodium carboxymethylcellulose (NaCMC) to form GNCs-NaCMC films. The films exhibited a broad absorption band in the range of 400–1750 nm. By placing the GNCs-NaCMC film in an EDFL cavity pumped by a 980 nm laser diode, stable passive Q-switching was achieved for a threshold pump power of ∼30 mW, and 3.2 μs pulses at 1560 nm with a repetition rate of 24.2 kHz were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 29 publications
3
87
1
Order By: Relevance
“…Additionally, because the response spectral range can be changed from the visible to the infrared by simply tuning the size, shape, or aggregation of the Au NPs, [ 1,8,30 ] these Au NPs could be theoretically proposed as alternative candidates in terms of broadband saturable absorbers. In previous experiments T. Jiang et al have successfully demonstrated Er-doped Q-switched lasers of 1.56 μm with well-designed Au nanorods as the switcher, [ 25,49 ] and we present Q-switching performance at 1.06 μm by modulation through Au NPs in this work, which verifi es that pulse modulation with Au NPs over this wide wavelength range is feasible.…”
Section: Communicationsupporting
confidence: 81%
“…Additionally, because the response spectral range can be changed from the visible to the infrared by simply tuning the size, shape, or aggregation of the Au NPs, [ 1,8,30 ] these Au NPs could be theoretically proposed as alternative candidates in terms of broadband saturable absorbers. In previous experiments T. Jiang et al have successfully demonstrated Er-doped Q-switched lasers of 1.56 μm with well-designed Au nanorods as the switcher, [ 25,49 ] and we present Q-switching performance at 1.06 μm by modulation through Au NPs in this work, which verifi es that pulse modulation with Au NPs over this wide wavelength range is feasible.…”
Section: Communicationsupporting
confidence: 81%
“…Recently, GNRs were also found to possess saturable absorption effect at longitudinal surface plasmon resonance (SPR) with Z-scan technique [29], indicating that GNRs could potentially find applications in Q-switched fiber lasers. Indeed, based on the GNRs-SA, the Q-switched erbiumdoped fiber laser operating at 1.55 μm waveband has been demonstrated recently [30,31]. In fact, it should be stressed that the position of longitudinal SPR can be conveniently tuned from the visible to the infrared region by varying the aspect ratio of GNRs, suggesting that the saturable absorption of GNRs could operate at different wavebands.…”
Section: Introductionmentioning
confidence: 98%
“…This phenomenon is known to occur in a medium with laser-active ions in which strong optical intensity can excite the ions to the upper energy level at a suffi ciently high rate so that they completely fi ll the upper energy states, leading to the saturation of the absorption. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In particular, very recently, saturable absorption performance has also been observed in TMDCs such as MoS 2 , MoSe 2 , MoTe 2 , WS 2 , WSe 2 , and WTe 2 , in which mono-and/or few-layer structures of TMDCs were tacitly prepared for use as SAs. [ 12 ] Although most of commercial saturable absorbers have so far been made of III-V semiconductors, other materials including carbon nanotubes, graphene, black phosphorus, gold nanoparticles, topological insulators, etc., have recently been investigated as novel saturable absorption materials.…”
mentioning
confidence: 99%